2012
DOI: 10.1139/x2012-110
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estimators in one-phase two-stage Poisson sampling in forest inventories

Abstract: This thesis investigates the performances of various estimators in one-phase (purely terrestrial) two-stage forest inventories, where trees in the first-stage are selected by concentric circles (approximate PPS) and a subset thereof are selected by Poisson sampling for further measurements to get an accurate estimation of the timber volume. Poisson sampling is used because it is easy to implement in field work. However, this comes with the drawback of a random second-stage sample size that can drive up the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…All the previous results can be easily generalized to cluster sampling and also to two-stage sampling (the local density Y(x) being simply replaced by the so-called generalized local density Y*(x)). The reader will find all the details and examples in Mandallaz (2013aMandallaz ( , 2013b and Mandallaz and Massey (2012).…”
Section: Generalization To Cluster and Two-stage Samplingmentioning
confidence: 99%
“…All the previous results can be easily generalized to cluster sampling and also to two-stage sampling (the local density Y(x) being simply replaced by the so-called generalized local density Y*(x)). The reader will find all the details and examples in Mandallaz (2013aMandallaz ( , 2013b and Mandallaz and Massey (2012).…”
Section: Generalization To Cluster and Two-stage Samplingmentioning
confidence: 99%
“…In the context of a two-stage forest inventory, Mandallaz and Massey (2012) have shown that it is possible to correct for model misspecification by using a two-stage HT estimator. The method could be adapted for an inventory such as the Spanish NFI.…”
Section: A B C Dmentioning
confidence: 99%
“…In sampling theory, there are two types of inference: design-based and model-based. In design-based inference, randomisation is used to select the population units to be measured; for statistical validity, estimators are constructed based on this randomisation [3][4][5]. An immediate implication is that the values of the variables of interest are treated as fixed; furthermore, the randomness in the estimators is only due to the random selection of the samples [6].…”
Section: Introductionmentioning
confidence: 99%